IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI PONOROGO NOMOR 60 TAHUN 2020 TENTANG PERCEPATAN PENANGGULANGAN KEMISKINAN BERBASIS DATA TERPADU KESEJAHTERAAN SOSIAL (DTKS) DI KECAMATAN NGEBEL KABUPATEN PONOROGO PROPINSI JAWA TIMUR - Sulistyarini, Tiena (JI@P, 2021)
The research aims to describe the extent to which the implementation of the Ponorogo Regent Regulation Policy Number 60 of 2020 concerning the Acceleration of Poverty Reduction Based on Integrated Social Welfare Data in Ponorogo Regency, East Java Province provides complete up to date and integrated poverty data information that will be used by the government in order to provide poverty management programs. particularly in the Non Cash Government Assistance (BPNT) Staple Food program for the community. BPNT-Staple Food is assistance provided by the Government for poverty alleviation and the welfare of Beneficiary Families. The background of the problem in this study is based on preliminary observations that many people do not understand the mechanism of the data collection process until the distribution results in the community not appreciating the government's commitment to poverty reduction.